Analysis of the expression patterns of the novel large multigene TRIM gene family (finTRIM) in zebrafish. Issue 66 (July 2017) - Luo, Kai; Li, Youshen; Xia, Lihai; Hu, Wei; Gao, Weihua; Guo, Liwei; Tian, Guangming; Qi, Zhitao; Yuan, Hanwen; Xu, Qiaoqing
Abstract: Tripartite motif (TRIM) proteins are receiving increased research interest because of their roles in a wide range of cellular biological processes in innate immunity. In zebrafish ( Danio rerio ), the functions of the finTRIM ( ftr ) family are unclear. In the present study, we investigated the expression pattern of ftr12, ftr51, ftr67, ftr82, ftr83, and ftr84 in zebrafish for the first time. The results showed that ftr12, ftr67, and ftr84 are maternally expressed in the oocyte and highly expressed at the early stage (0–4 hpf) of embryo ( P  < 0.05), suggesting their involvement in the embryonic innate defense system. The ftr82 gene was highly expressed at 8 hpf ( P  < 0.05), which implied that the embryos could synthesize their own immunity-related mRNAs. However, ftr51 and ftr83 were highest at 8 hpf (2.33 and 51.53 relative to β-actin respectively) and might mediate embryonic development. The expression levels of ftr12, ftr51, and ftr67 were highest in the gill, intestines, and liver, respectively. Ftr82, ftr83, and ftr84 were predominantly expressed in the kidney, suggesting that these finTRIMs might play roles in both immunity and non-immunity-related tissue compartments. Zebrafish embryonic fibroblast (ZF4) cells were infected with Grass carp reovirus (GCRV) and Spring viremia of carp virus (SVCV). During GCRV infection, the expression of ftr12 was significantly upregulated from 12 h to 24 h; and ftr51 and ftr67 increased from 3 h to 12 h. The expressions of ftr82, ftr83, and ftr84 were only upregulated at 12 h, 12 h, and 24 h, respectively. All of these genes were significantly downregulated at 48 h ( P  < 0.05). Challenge with SVCV upregulated the expressions of ftr12 and ftr51  at 12 h and 48 h ( P  < 0.05), respectively, and ftr67 reached its highest expression level at 3 h. ftr82 showed only a slight upregulation at 6 h and 48 h, and ftr83 and ftr84 were consecutively increased, reaching their highest levels at 12 h ( P  < 0.05). Meanwhile, ftr67 and ftr83 were significantly downregulated at 48 h ( P  < 0.05). Our research demonstrated that ftr12, ftr51, ftr67, ftr82, ftr83, and ftr84 probably have important roles in innate immune responses and in non-immunity-related tissues. Highlights: This manuscript analysed the expression of several TRIM family members in zebrafish. The common viruses (GCRV and SVCV) can induce the transcript level of ftr12, ftr51, ftr67, ftr83, and ftr84. The expression pattern of several TRIM family members was quite different after challenged with different virus.